Perkembangan Hukum Keluarga di Tunisia - Lukman Hakim (Prodi Pendidikan Agama Islam Fakultas Tarbiyah IAINU Kebumen, 2022)
Islamic family law in Tunisia is unique because of Tunisian radicalism. This is because the process of formulating and structuring Islamic family law in Tunisia is not just an attempt to codify (bookkeeping) the Maliki school of law. However, these are also progressive and revolutionary steps in an effort to legalize and regulate administration in the field of law, particularly with regard to family law. This is evidenced by the birth of the Tunisian Code of Personal Status. Judging from the historicity of the formation of the CPST, it was heavily influenced by France. In addition, there are also Nationalists who have a secular educational background. The legal reforms carried out by the Tunisian government, in terms of existing problems, do not intend to deviate and abandon the principles of Islamic law, but rather are caused by the government's desire to ensure the welfare, peace and benefit of the Tunisian nation and people themselves.